OBSTETRICAL ACUTE RENAL FAILURE: A CHALLENGING MEDICAL COMPLICATION - Rizwan, Naushaba; Uddin, Syed Farhan (Journal of Ayub Medical College Abbottabad, 2011)
Background: Acute renal failure (ARF) is a syndrome characterised by rapid decline in glomerular filtration rate and retention of nitrogenous waste products such as urea and creatinine. The objective of this study was to study the prevalence, risk and outcome of women with obstetrical renal failure. Methods: This observational study was conducted in Department of Obstetrics and Gynaecology, Liaquat University Hospital, Hyderabad, Pakistan from October 2009 to September 2010. Thirty-five patients with obstetrical acute renal failure were included in the study, patients with chronic renal diseases, hypertension, diabetes mellitus and renal stones were excluded from the study. A detailed history was followed by thorough examination and investigation. Their clinical history, physical examination and intake/urine output was recorded. Routine laboratory investigations were done related to each case and specialised investigations like renal scan, renal ultrasonography and renal biopsies were performed in selected cases where recovery was delayed for more than 3 weeks. Results: Total numbers of admissions in obstetric ward were 3,285. Pregnancy related acute renal failure was found in 35 (1.065%) women. Age ranged from 18-40 years. Most of the women belonged to age group 30-35. Out of 35 women 31.42% had postpartum haemorrhage. Ante partum haemorrhage was found in 25.71%, Eclampsia in 17.14%, DIC in 14.28%, and sepsis in 11.42%. Anuria was observed in 25 patients, remaining presented with oliguria (28.57%). Haemodialysis was done in 75% of patients, others were managed conservatively. Complete recovery was observed in 53% cases. Maternal mortality was 25.71% and foetal mortality was 22.85%. Conclusion: Pregnancy related ARF is one of the most common causes of ARF, it is a dangerous complication of pregnancy which carries very high mortality and morbidity. Keywords: acute renal failure, prevalence, outcome, complications, maternal, foetal, obstetrical